Using Participatory Rural Appraisal for a Community Needs Assessment in Timor-Leste - Kim E. Dooley; Catherine Dobbins; Leslie D. Edgar (Journal of International Agricultural and Extension Education, 2018)
Conducting timelyand effective needs assessments in the field is important for international development work. In many cases, a researcher has only a couple of hours to build rapport with a community, visually examine the state of the field, and conduct the needs assessment and achieve open, honest, and valid data. Working with translators further constrains the process by cutting available time. Thus, research focused on conducting these types of international assessments is valuable. This study aimed to identify the key needs of theFatubesi community in Timor-Leste using a combination of techniques for Participatory Rural Appraisal (PRA)—a transect walk and a small group discussion that included guided questions and ranking priorities. PRA is context specific and emphasizes facilitation of co-learning between local knowledge and outside expertise (Toness, 2005). Water, new fencing, and technical training/seeds were identified as the top three priorities for the community and their gardens, and the transect walk revealed issues with infrastructure that provided visual context for the small group discussion. The results of this study reflect the unique challenges faced by many communities in international development settings. The techniques described in this article are beneficial when used together for PRAto shift roles from expert facilitator to local empowerment.
Keywords: Participatory Rural Appraisal; Needs Assessment; Timor-Leste; Community Needs